EKSISTENSI ALAT BUKTI SURAT REKOMENDASI ASESMEN TERPADU DALAM PERKARA NARKOTIKA: STUDI PUTUSAN PENGADILAN NOMOR 51/PID.SUS/2025/PN.SLK: The Existence Of Integrated Assessment Recomendation Letter Evidence In Narcotics Cases: A Study Of Court Decision No. 51/Pid.Sus/2025/PN.Slk - Kayla Jamela Galent; Setiyono (Reformasi Hukum Trisakti, 2026)
The BNN integrated assessment recommendation letter is an important basis for determining the feasibility of rehabilitation of narcotics abusers in accordance with Article 54 of Law Number 35 of 2009 concerning Narcotics. This document includes letter evidence as referred to in Article 184 paragraph (1) letter c of the Criminal Procedure Code and contains a medical assessment as expert testimony. However, these recommendations have not always been considered, as reflected in the Solok District Court Decision Number 51/Pid.Sus/2025/PN.Slk which imposes a prison sentence even though the defendant meets the rehabilitation criteria based on the Supreme Court Circular Letter Number 4 of 2010. The formulation of the problem in this study is how the strength of the evidence of the BNN principle recommendation letter in the case of narcotics crimes according to the criminal procedure law in decision number 51/pid.sus/2025/PN.Slk which is associated with the Supreme Court Circular Letter Number 4 of 2010. This study uses normative legal research methods with a legislative approach and a case approach. The results of the discussion and conclusion show that the BNN assessment recommendation letter has formal and material evidentiary strength that should be considered optimally as part of the due process of law.